2001
DOI: 10.2460/javma.2001.218.1436
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Clostridium difficile-associated diarrhea in two cats

Abstract: Two adult cats from the same household developed acute diarrhea. Clostridium difficile toxins were detected in the feces of both cats, whereas other recognized causes of diarrhea were not identified. Supportive medical treatment and metronidazole were administered and both cats responded well. A fecal sample obtained from 1 of the affected cats after treatment and a fecal sample obtained from a clinically normal cat in the household did not contain C difficile toxins. The role of C difficile in enteric disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…In addition, all animal and human isolates displayed 39-bp deletions in tcdC, and most (45/47; 96%) were binary toxin positive. Although C. diffi cile is recognized as a cause of disease in several animal species (19)(20)(21)(22), little investigation has been conducted on the potential for interspecies transmission of C. diffi cile to humans. Previous studies have suggested the possibility of C. diffi cile transmission between humans and domestic pets (23,24), but no interspecies transmission has been documented, and few studies have examined the possible link between CDAD in food animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all animal and human isolates displayed 39-bp deletions in tcdC, and most (45/47; 96%) were binary toxin positive. Although C. diffi cile is recognized as a cause of disease in several animal species (19)(20)(21)(22), little investigation has been conducted on the potential for interspecies transmission of C. diffi cile to humans. Previous studies have suggested the possibility of C. diffi cile transmission between humans and domestic pets (23,24), but no interspecies transmission has been documented, and few studies have examined the possible link between CDAD in food animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…162 Clostridium difficile-associated disease in nonhuman primates is rarely reported, but Old World and New World monkeys are known to be susceptible to naturally acquiring disease and to the effects of purified toxins. Postantibiotic diarrhea in juvenile and adult cotton-top tamarins (Saguinus oedipus) was reportedly attributed to C. difficile.…”
Section: Sensitivity and Host Susceptibilitymentioning
confidence: 99%
“…Clostridium difficile-associated disease develops spontaneously in a variety of other species including horses (Equus caballus), 93 hares (Lepus spp. ), 32 pigs (Sus scrofa), 156 nonhuman primates (Macaca spp., Pongo pygmaeus, and Saguinus oedipus), 128,150 domestic dogs (Canis familiaris), 161 domestic cats (Felis catus), 162 ostriches (Struthio camellus) 42 and black-tailed prairie dogs Vet Pathol 43:225-240 (2006) (Cynomus ludovicianus). 104 This review addresses the pathogenesis of C. difficile-associated disease (CDAD) and compares the lesions and clinical conditions among known susceptible species.…”
mentioning
confidence: 99%
“…While signs of disease could range from mild self-limiting diarrhoea to chronic or fatal diarrhoea (Berry and Levett 1986), the relevance of the bacterium in small veterinary clinics is still uncertain (Weese 2011;Busch et al 2014). Different other studies have associated the presence of C. difficile in faeces with diarrhoea in dogs and cats (Weese et al 2001a;2001b;Weese and Armstrong 2003;Koene et al 2012;Wetterwik et al 2013). However, dogs can also be healthy carriers of C. difficile strains belonging to human epidemic PCR-ribotypes (Schneeberg et al 2012;Silva et al 2013b;Spigaglia et al 2015), with a high colonisation in the first period of live (Perrin et al 1993;Á lvarez-Pérez et al 2015).…”
mentioning
confidence: 99%